Influence of seasonality on macroinvertebrate diversity associated with the aquatic fern Salvinia biloba Raddi - Coutinho, Rennan Leite Martins; Lancellotti, Isabella Rodrigues; Flores, Arthur Ribeiro; Santos, Marcelo Guerra (EntomoBrasilis, 2020)
Abstract. The genus Salvinia is composed of fast-growing floating ferns, capable of surviving in different environmental conditions. Some authors suggest that the relationships between this genus and macroinvertebrates may serve as water quality indicators. The present study aimed to determine the influence of seasonality and water quality on macroinvertebrate diversity associated with the Salvinia biloba Raddi. Water and fern were collected in rainy and dry seasons and was conducted a microbiological analysis of the water, as well as, the area of fern cover on the water, richness, and density of macroinvertebrates. Microbiological analysis of the water detected > 5,700 CFU/mL (rainy season) and 175 CFU/mL (dry season) of heterotrophic bacteria and was positive for total thermotolerant coliforms. The S. biloba cover on the water surface was 100% in the rainy and 30% in the dry season. In the rainy season, 142 macroinvertebrates were identified, divided into 12 morphospecies, with a density of 434 individuals/m3. In the dry season, there were 419 individuals in 14 morphospecies, with a density of 2,076 individuals/m3 exhibited. The highest species density recorded in the rainy season was for Chironomidae sp.1 (Diptera) (57.71%) and Odonata Zygoptera sp.1 (17.44%), and in the dry season, Chironomidae sp.2 (73.98%) followed by Gerromorpha sp.1 (Hemiptera), with 9.54%. The Sørensen similarity index between the two seasons was 53.84%. The higher density of Gerromorpha sp.1 in the dry season may indicate an increase in environmental integrity.